God of justice: ritual healing and social justice in the central Himalayas - Sax, William Sturman (Oxford University Press, 2009)
Based on ten years of ethnographic fieldwork, this text offers a fascinating glimpse into the world of cursing, black magic, and ritual healing in the Central Himalayas of North India.